PATHOGENESIS OF CHANGES IN THE MOUTH WITH SUGAR DIABETES - Xujakulov Davron Abdikhakimovich (TADQIQOTLAR.UZ, 2023)
Annotation. Diabetes mellitus (lat. diabetes mellitus) is a group of endocrine diseases that develop as a result of an absolute or relative deficiency of the hormone insulin, resulting in a persistent increase in blood glucose.